1982
DOI: 10.1152/jappl.1982.53.3.660
|View full text |Cite
|
Sign up to set email alerts
|

A critical value for O2 transport in the rat

Abstract: Rat skeletal muscle O2 uptake (VO2) has been reported to be supply dependent even at normal blood flow rates. To find the point at which whole-animal VO2 became dependent on total O2 transport (TOT), intact anesthetized rats were ventilated under hypoxic, normoxic, and hyperoxic conditions while either normovolemic or hypovolemic. In this manner, TOT (cardiac output X arterial O2 content) was varied over a range of 5-80 ml . kg-1 . min-1 . VO2 was measured in a closed-circuit, double servospirometer system. O2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 0 publications
3
19
2
Order By: Relevance
“…Certainly, it was demonstrated in dog skeletal muscle that, even though pop was usually constant over a wide range of blood flows, it was dependent on flow in preparations in which vasodilator responses to local metabolic influences were absent (Duran & Renkin, 1974). Moreover, our results are consistent with others obtained in anaesthetized rats which showed that during systemic hypoxia, whole body Vo,, which would be expected to strongly reflect Vo, of skeletal muscle, did not become dependent on total 0, delivery (cardiac output x Ca, , , , ) until Ca,O, was below -13 ml (1 00 mI)-' (Adams et al 1982). This is below the level reached in the present study during 8 YO 0, (Fig.…”
Section: Acute ~~~~~~A In N Ratssupporting
confidence: 91%
“…Certainly, it was demonstrated in dog skeletal muscle that, even though pop was usually constant over a wide range of blood flows, it was dependent on flow in preparations in which vasodilator responses to local metabolic influences were absent (Duran & Renkin, 1974). Moreover, our results are consistent with others obtained in anaesthetized rats which showed that during systemic hypoxia, whole body Vo,, which would be expected to strongly reflect Vo, of skeletal muscle, did not become dependent on total 0, delivery (cardiac output x Ca, , , , ) until Ca,O, was below -13 ml (1 00 mI)-' (Adams et al 1982). This is below the level reached in the present study during 8 YO 0, (Fig.…”
Section: Acute ~~~~~~A In N Ratssupporting
confidence: 91%
“…The critical oxygen delivery, below which VO 2 becomes supply dependent, has not been reported in rabbits. In multiple species, however, the onset of supply dependence is associated with reductions of mixed venous saturations to the range of 30 -50% (1,8,36,60), well below the lowest venous saturation of 64% observed in the current study. The paired differences in Sv O 2 between the two groups (high rate, low PEEP vs. low rate, high PEEP), therefore, support the cardiac output data measured by pulse contour analysis.…”
Section: Discussioncontrasting
confidence: 65%
“…Under most physiologic conditions in which SOT is independently reduced, oxygen consumption initially remains unchanged and then is decreased by further, more severe limitations in oxygen transport (26)(27)(28). With the decline in oxygen transport and consumption there is metabolic evidence of tissue hypoxia, reflected by an increase in arterial blood lactate concentration (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%